ANTI-ANGIOGENIC ACTIVITY OF THE EXTRACTED FERMENTATION BROTH OF AN ENTOMOPATHOGENIC FUNGUS, CORDYCEPS MILITARIS 3936 - Tuli, Hardeep S.; Sandhu, S. S.; Sharma, Anil K.; Gandhi, Puneet (International Journal of Pharmacy and Pharmaceutical Sciences, 2014)
Objective: Cordyceps militaris is an entomopathogen and known to exhibit significant therapeutic potential. In the present study, we aimed to extract various fractions (aqueous; hexane; chloroform & butanol) including active ingredient cordycepin from fermented broth of Cordyceps militaris followed by their evaluation as anti-angiogenic agents. Methods: The bioactive metabolite, cordycepin and various Cordyceps derived fractions were isolated from liquid culture of Cordyceps militaris using solvent-solvent extraction method followed by purification on silica gel column chromatography. Furthermore anti-angiogenic properties of extracted fermentation broth were also investigated using chorioallantoic membrane (CAM) assay. Results: Butanolic fractions, demonstrated the highest anti-angiogenic activity followed by chloroform, hexane and aqueous fractions of extracted fermentation broth. Anti-angiogenic studies for extracted cordycepin showed that 40 Âµg/egg dosage of cordycepin was sufficient to inhibit the branching of blood vessels significantly (~50%) in a CAM assay. Conclusion: It is concluded that butanolic extract/cordycepin from fermented broth of Cordyceps militaris potentially inhibits the angiogenesis and suggests that the inhibition of angiogenesis is one of the mechanisms by which Cordyceps militaris can mediate an anti-cancer effect.